Isolation and Screening the Symbiont Bacteria of the Sponge Dragmacidon sp from Manado Bay, North Sulawesi that Producing Chitinase and Protease - Sembiring, Sindiy Cloudya; Warouw, Veibe; Wullur, Stenly; Bara, Robert A; Salaki, Meiske S.; Ginting, Elvy Like (Jurnal Ilmiah Platax, 2021)
Enzymes are important in the technology industry and hydrolytic enzymes, such as chitinase and protease are commonly used for it. Various types of microorganisms such as bacteria can produce hydrolytic enzymes. Sponge-associated bacteria are excellent sources of extracellular hydrolytic enzymes because the surface and internal spaces of sponges are richer in nutrients. The aim of this study was to isolate and screen the bacteria of the sponge Dragmacidon sp symbiotic from Manado Bay, North Sulawesi that producing chitinase and protease Symbiont bacteria were grown in Zobell 1226 E medium with a dilution of 10-4. Bacterial isolation was carried out based on the morphological characteristics of the colony. Chitinase and protease activity was carried out by growing each bacterial isolate in chitin and protein media at 36oC for 48 hours. Chitinase and protease activities were indicated by the formation of a clear zone around the bacterial colony, however, the clear zone for chitinase activity was observed after pouring the Lugol's solution. Based on this study, 8 isolates bacteria of the symbiotic spongy Dragmacidon sp from Manado Bay, North Sulawesi were isolated based on morphological characteristics. The colony of the bacteria is generally white with an irregular shape. Four isolates, namely 1, 2, 3, and 8 had chitinase activity with chitinolytic indexes were 1.7; 1.5; 1.4, and 1.3, respectively. Six isolates, namely 1, 2, 3, 4, 5, and 6 had protease activity with proteolytic indexes were 1.4; 1.8; 3.1; 1.3; 1.8; and 2.5, respectively.Keywords: Bacteria; Chitinolytic; Proteolytic; Symbiont; SpongeAbstrakEnzim menempati posisi penting dalam bidang teknologi dan industri. Enzim yang banyak digunakan dalam bidang industri adalah enzim hidrolase. Enzim dapat diisolasi dari berbagai jenis mikroorganisme seperti bakteri. Bakteri yang berasosiasi dengan spons merupakan sumber enzim hidrolitik ekstraseluler yang sangat baik karena permukaan dan ruang internal spons lebih kaya nutrisi. Penelitian ini bertujuan untuk mengisolasi dan menguji aktivitas kitinase dan protease bakteri simbion spons Dragmacidon sp dari Teluk Manado. Bakteri simbion spons ditumbuhkan dalam media Zobell 1226 E pada pengenceran 10-4. Isolasi bakteri dilaksanakan berdasakan karakteristik morfologi. Aktivitas kitinase dan protease dilaksanakan dengan menumbuhkan setiap isolat bakteri dalam media kitin dan protein pada suhu 36oC selama 48 jam. Aktivitas kitinase dan protease ditandai dengan terbentuknya zona bening di sekitar koloni bakteri yang mana untuk kitinase diamati setelah diberi larutan lugol. Berdasarkan penelitian ini, 8 isolat bakeri simbion spon Dragmacidon sp dari Teluk Manado, Sulawesi Utara berhasil diisolasi berdasarkan karakteristik morfologi. Isolat bakteri umumnya berwarna putih dengan bentuk ireguller. Empat isolat yakni 1, 2, 3, dan 8 memiliki aktivitas kitinase dan enam isolat yakni 1, 2, 3, 4, 5, dan 6 yang memiliki aktivitas protease. Indeks kitinolitik dari masing-masing keempat isolat bakteri secara berturut turut adalah 1,7; 1,5; 1,4; dan 1,3 dengan kategori bernilai rendah dan indeks proteolitik adalah 1,4; 1,8; 3,1; 1,3; 1,8; dan 2,5 dengan kategori bernilai rendah sampai tinggi.Kata kunci: Bakteri; Kitinolitik; Proteolitik; Simbion; Spons